Factors affecting participation of BRICS Countries in Global Value Chains (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
In the last two decades there has been a higher degree of interdependency in global trade and production network. The internationalisation of the supply chain has brought new term to the forefront known as Global Value Chains (GVC). Now the production is not confined to the one country but spread across number of countries and there is increased trade of intermediate goods. The reduction in trade costs, increased trade facilitation, reduction in tariffs, liberalisation of domestic economy, progress in the field of ICT etc are some of the factors that have made GVC workable on the international platform.